Curcumin displays enhanced solubility and antibacterial activities when complexed with the cell penetrating peptide pVEC - SARIYAR AKBULUT, BERNA (My University, 2022)
Curcumin is among phytochemicals with increasing popularity; unfortunately, its therapeutic potential is restricted due to poor water solubility and bioavailability. The current work undertakes the effort to improve the therapeutic potential of curcumin by complexing it with a cell penetrating peptide using copper ions. A mononuclear complex was synthesized from copper(II) acetate and curcumin. Then this complex was conjugated to the cell penetrating peptide, pVEC. The structural characterization of the complexes was achieved using UV-Vis and Fourier transform infrared spectroscopies. Dynamic and electrophoretic light scattering measurements have confirmed the complexation of curcumin with the peptide to form nanoparticles. Both solubility and kinetic stability of curcumin greatly improved upon complex formation with pVEC through copper ions. Then the antibacterial activity of curcumin in the complex was tested. The amount of curcumin in the minimum inhibitory concentration was similar to 30, similar to 8, and similar to 15 fold lower, respectively for Escherichia coli, Bacillus subtilis, and Staphylococcus aureus when complexed with pVEC; however, this improvement was specifically noteworthy for the gram-negative E. coli since the contribution of pVEC in the complex to the observed activity was negligible in this bacterium. With enhanced solubility and stability, metallo curcumin conjugated pVEC complex possesses potential for different therapeutic applications.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Klinik Biyokimya; Kanser Araştırmaları; Moleküler Biyoloji; İlaç Keşfi; Yaşlanma; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Biyokimya; Yapısal Biyoloji; Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Biochemistry; Structural Biology; Curcumin; Cell penetrating peptide; Copper; Solubility; Stability; Antimicrobial activity; IN-VITRO; AQUEOUS SOLUBILITY; NATURAL-PRODUCTS; METAL-COMPLEXES; NANOPARTICLES; STABILITY; DEGRADATION; ACID; DRUG; ENCAPSULATION; Curcumin; Cell penetrating peptide; Copper; Solubility; Stability; Antimicrobial activity